Earlier Development of Limb Ulcers, Digital Bone Infarction and Pulmonary Hypertension in a Patient with SLE- A Rare Case Report - Hezbullah, Muhammad; Chakrabarty, Shishir Ranjan; Sultana, Sharifa; Tohin, Manwarul Haque; Nahar, Kamrun (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Systemic lupus erythematosus (SLE) is a multiorgan autoimmune disease in which skin is involved in up to 85% of cases. Lower extremity ulcers are an infrequent but disabling complication of SLE. Critical peripheral ischemia (CPI) is also an uncommon but potentially devastating feature of SLE. We reported a case o f SLE who presented with multiple ulcers along with digital infarcts of upper and lower limbs. She had features of digital bone infarct of left hand and right foot. She also had features of pulmonary interstitial involvement with pulmonary hypertension. All of these features were found within three months of disease onset which is very rare. She was treated with intravenous Methylprednisolone followed by oral Prednisolone, Hydroxychloroquinine, Azathioprine, Diuretic, Bosentan, Aspirin and Nifedipine in combinaton. Later warfarin was added after one month. She showed significant improvement after three months of treatment. J Bangladesh Coll Phys Surg 2017; 35(3): 150-154